[Briefe] Vier Briefe Schillers - Schiller, Friedrich,Boxberger, Robert,Böttiger, Carl August,Becker, Gottlieb Wilhelm,Frommann, Carl Friedrich Ernst,Stein, Friedrich Constantin von (In:Archiv für Litteraturgeschichte;Leipzig : Teubner, 1869;15(1887), Seite 296-299, 1887)
An W. G. Becker, 1802; an Frommann 1803; an Böttiger (?) 1803; an Fritz v. Stein 1805